The Interprofessional Education (IPE): The Community Outcomes of Health Services within Collaboration Practices in Faculty of Medicine Sebelas Maret University - Kevin Pieter Toman; Ari Natalia Probandari; Amandha Boy Timor Randita (Nexus Pendidikan Kedokteran dan Kesehatan, 2016)
Introduction: Interprofessional Education (IPE) is a collaborative practice with two or more health professions that each studying the role of each health profession to improve collaboration and quality of health care. This study aimed to determine the outcomes of interprofessional approach, medical and midwifery students, based on the public perception of the health services using community-based IPE learning method. Methods: This study was a qualitative research, conducted in Puskesmas Sangkrah in January 2016. The subject of the research were patients and their families who received medical care in Faculty of Medicine Sebelas Maret University IPE program in December 2015. The sampling technique was purposive sampling with typical type of sample. The data was taken by using the in-depth interview on the subject with the amount of data retrieval determined by saturation data. The research instrument is the researcher himself. Interview guidelines referring to instruments Attitudes Toward Health Care Teams (ATHCT) Scale were translated and modified. Data were analyzed using thematic content analysis. Results: The outcomes of health services by interprofessional education learning method in faculty of medicine sebelas maret university, it was obtained the category of comprehensive of care, continuity of care, communication between team and patient, and team collaboration. Conclusions: The community founds the outcome of health services with interprofessional education is good. Through public perception, we obtained two perceptions of interprofessional education, it was found that good health care can be obtained through the implementation of a good IPE by implementing patient-centered care and good communication among the health care team with the patients and their families, and also among members in the healthcare team.Keywords: community, interprofessional education (IPE), outcome